(3cGed GdUfGYI GdWHjIs - (3Ydj Hf YHGS GdeLhSj,fMh (B400 (3g`s
(3ChdgG (B:s
(3eHJhQ GdChd hChd GdehLhO efg (B: (3eOGhGI GdeGOI GdMGOKI ef ZjQ bQMI , hdG eOGhGI GdCKQ hGdHjGV hdG eOGhGI GdfJD s
(3BNQgG (B:s
(3aGYde Pdc , agPG CeG CQOfG JfHjg ef CeQ GdYdGeGJ s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B162s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B191 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B328 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdWHs